DIMENSI PERSONAL DAN DIMENSI KOLEKTIF DALAM BUDAYA POPULER: KAJIAN PSIKOLOGI ANALITIS DALAM FILM FATE: THE WINX SAGA - Afifulloh, M (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
This article tries to explore some of the implication of Carl Gustav Jung’s theory of personal dimension and collective dimension as represented by the characters in Fate: The Winx saga. This film is produced by Netflix and released on 22 January 2021. In this research, film is assumed as media to validate Jung’s theory about human psyche. This research is a qualitative descriptive. The data were processed by analyzing, categorizing, and interpreting the visual codes provided by the film. Therefore, the meaning can be theoretically drawn. The result of this study shows that the personal and collective dimensions offered by Jung are owned by the characters in the film. The personal dimension manifests in the Ego in the form of emotions and memories of the past. This personal dimension is represented through the characters such as Bloom, Musa, and Terra. While the collective dimension can be explained through the persona, shadow, anima and animus shared by all the characters in the film.